Biodegradable materials for transient organic transistors - Stephen, Meera (2023)
Electronic devices that can physically disappear in a controlled manner without harmful by-products unveil a wide range of opportunities in medical devices, environmental monitoring, and next-generation consumer electronics. Their property of transience is indispensable for mitigating the global problem of electronic waste accumulation. Additionally, transient technologies that are biocompatible and can be biologically resorbed are of great potential for applications in temporary medical implants, since it eliminates the need for expensive device recovery surgery. Transistors are the key building blocks of modern electronics, and their fabrication using organic materials is beneficial due to their low cost, unprecedented flexibility and facile processing. This contribution reviews the technological application of biodegradable materials in four major classes of organic transistors, namely organic field-effect transistors (OFETs), organic synaptic transistors, electrolyte-gated OFETs, and organic electrochemical transistors. The fundamental biodegradation mechanism is discussed in detail, followed by a perspective of various biodegradable materials utilized as active semiconductors, dielectrics, electrolytes and substrates in the various types of organic transistor devices. This contribution comprehensively discusses the role and application of biodegradable materials in all of the key modern-day organic transistors, highlighting their unique properties that allow the fabrication of biodegradable, eco-friendly, and sustainable devices.